The scarlet letter [compact disc, unabridged] - Hawthorne, Nathaniel, 1804-1864 (Classic collection (Brilliance Audio (Firm)), 2015)
The story opens in Puritan Boston, a settlement only fifteen or twenty years old. A young woman stands on a scaffold clasping a three-month-old baby. As a married woman with a missing husband and a new baby, Hester Prynne could have been sentenced to death for the crime of adultery. Instead she is condemned to always wear the letter A as a badge of her shame. As she stands there, she sees her long-missing husband, who has been held captive by Indians. While the town chorus is murmuring against her and her old and unattractive husband stares silently at her, the young and handsome clergyman publicly demands the name of her partner in crime; while desperately praying that she won't reveal him.